Contributions to the conservation and promotion of the food heritage from a University Community Work of the School of Nutrition of the University of Costa Rica (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This article describes the main contributions of the TCU-486 project of the School of Nutrition of the University of Costa Rica (UCR) in the conservation and promotion of the food heritage of Costa Rica. The review of reports and resources produced during the period 2003-2023 was carried out with emphasis on the themes, participating actors, achievements and challenges. There has been the participation of 440 students from 25 different majors, with the investment of 132,000 hours of work in communities, mainly in the Greater Metropolitan Area, and the active participation of the elderly population as bearers of the tradition. The project has been linked to 71 entities between public institutions, community organizations, Municipalities, among others, which has allowed the development of educational, promotional and action research activities. The main challenges are the sustainability of the actions, the greater projection in remote areas and the consistency in student participation, given the school schedules and the monitoring required in the communities. It is evident how this social action project responds to the commitment to generate spaces for reflection, encounter and community and intergenerational dialogue, as well as the link with other national bodies in favor of the conservation and promotion of cultural heritage.
Keywords: traditional food; food culture; Costa Rica; university communal work; nutrition